DAMPAK SOSIAL, EKONOMI DAN LINGKUNGAN PENGEMBANGAN KAWASAN EKOWISATA PANTAI LABUHAN BANGKALAN MADURA - Sugiarti, Teti; Kryshna Pratama, Guntur; Subari, Slamet (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 18 No 2 (2024), 2024)
The development of mangrove-based coastal ecotourism is expected to make a significant contribution to local economic development. The purpose of this study is to determine the socio-economic and environmental impacts of the development of Ecotourism Labuhan Bangkalan Beach (EPLB) Madura. This research uses a descriptive method with purposively selected sources. Primary data collection was conducted through interviews with people inside and outside the tourist area. Labuhan Village people who carry out activities inside and outside the area are managers, workers, traders, and the community. The results showed that the development of EPLB tourism objects had a positive and negative impact on socio-economic and environmental changes in the Labuhan Bangkalan Village community. Social aspects of positive impacts include changes in people's lifestyles, community support for developing sustainable tourism objects, community involvement in sustainable tourism development, and the establishment of cooperation between tourism object managers and related parties. The negative impacts are the potential for increased conflict between communities, noise, security and free association. From the economic aspect, there are new job opportunities in the tourist area, new business opportunities such as selling food and drinks inside and outside the tourist area, and increasing community income. Negative impacts that occur are uneven income and increased living costs. From the environmental aspect, there is an increase in local community knowledge about the benefits of mangroves, improvement of infrastructure to tourist areas such as roads and lighting, and handling local waste generated by visitors and surrounding households that are stuck to mangrove roots. Negative impacts include domestic waste disposal and pollution. Keywords: Labuhan Beach Ecotourism; Mangrove; Socio-economic & Environmental Impacts; Labuhan Village; Mixed Methods